Romperod, diameter growth in uneven-sized spruce stand - Fagerberg, Nils (Linnaeus University, 2022)
The data consists of long term diameter growth observations of uneven-sized Norway spruce dominated stands. The site has been managed with continuous individual tree selection for at least 100 years. There are two plots with different timing of cutting treatments. Height and age measurements of sample trees. One of the plots have coordinate set tree positions. Initial revision is 1989. The first plot consists of 209 tree observations and the second plot consists of 257 tree observations (at first revision point).

The Excel file [Romperöd uniform data copy of version 3.xlsx] contains all data from all revisions between 1989 and 2015. This data is without coordinates of the tree positions. The data file contains information that links the tree identities between the two data files.

The Excel file [Romperöd level 1b copy.xlsx] contains data from an extended revision of the thinned plot where the trees were also coordinate set. 74 of the trees have extended information on annual growth ring, root incidence, crown shape and height.

Dataunderlaget består av observationer av diametertillväxt i ett fullskiktad grandominerat skogsbestånd. Försöksytan har hanterats med blädning/selektiv avverkning i minst 100 år. Det finns två provytor med olika tidpunkter för avverkning. Höjd- och åldersmätningar finns på vissa provträd. En av ytorna har koordinatinmätta trädpositioner. Den första revisionen är gjord 1989. Den första ytan består av 209 trädobservationer och den andra ytan består av 257 trädobservationer (vid första revisionen).

Excel-filen [Romperöd uniform data version 3 snd.xlsx] innehåller all data från samtliga revisioner mellan 1989 till 2015. Dessa data är utan koordinatsättning av träden. Datafilen innehåller information som länkar trädidentiteterna mellan de två datafilerna.

Excel-filen [Romperöd nivå 1b snd.xlsx] innehåller data från en utökad revison av den gallrade ytan där träden även koordinatsattes. 74 stycken av träden har utökad information om årsringstillväxt, rötförekomst, kronform och höjd.
Romperöd, diametertillväxt i skiktad granskog
Keywords: tree growth; Norway spruce; Gran; continuous cover forestry; kontinuitetsskogsbruk; individual tree selection; individuella trädval; diameter increment; diametertillväxt; uneven-sized forest stand; skiktat skogsbestånd; multi-layered forest stand; flerskiktat skogsbestånd; long-term measurements; långsiktiga mätningar; uneven-aged forest stand; olikåldrigt skogsbestånd; selective cutting; selectiv avverkning; Forest Science; Skogsvetenskap